2001
DOI: 10.1177/0310057x0102900206
|View full text |Cite
|
Sign up to set email alerts
|

Total Intravenous versus Inhalational Anaesthesia for Colonoscopy: A Prospective Study of Clinical Recovery and Psychomotor Function

Abstract: A randomized, prospective study was conducted on 69 patients comparing recovery after two different anaesthetic techniques for ambulatory colonoscopy. Thirty-five patients received an intravenous fentanyl (1 µg/kg), midazolam (0.05 to 0.075 mg/kg) and propofol (10 to 20 mg boluses as required) combination. 34 patients received sevoflurane in 67% nitrous oxide. Drug administration was titrated to clinical signs. At baseline and 30, 60, 90 and 120 minutes after the procedure patient performance on a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Theodorou et al 18 demonstrated impaired performance up to 120 min after propofol/ midazolam/fentanyl or nitrous oxide/sevoflurane sedation for colonoscopy. In contrast, Moerman et al 19 found no cognitive impairment after 15 min in colonoscopy patients sedated with propofol or remifentanil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theodorou et al 18 demonstrated impaired performance up to 120 min after propofol/ midazolam/fentanyl or nitrous oxide/sevoflurane sedation for colonoscopy. In contrast, Moerman et al 19 found no cognitive impairment after 15 min in colonoscopy patients sedated with propofol or remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…However, the changes in cognitive function between discharge and baseline were not significantly different between the two groups. At discharge, 18.5% of patients were cognitively impaired to an extent equivalent to a bloodalcohol concentration of 0.05%. Sedation with propofol plus midazolam and/or fentanyl produced better operating conditions than sedation with propofol alone and was associated with shorter procedure times.…”
mentioning
confidence: 99%
“…Patient non-compliance is an obstacle to screening and surveillance programs for colorectal cancer. Several methods had been developed to minimise patient discomfort during colonoscopic examination, such as use of relaxing music, electroacupuncture, conscious sedation and general anaesthesia (12)(13)(14)(15). Benzodiazepines and opiates are commonly used for sedation.…”
Section: Discussionmentioning
confidence: 99%
“…It may delay time to recovery landmarks such as discharge from intensive care to ward and home readiness, it may result in poorer pain management or failure to complete the important cardiac rehabilitation programs that follow CABG surgery. Consequently, the meaningfulness of POCD may be better understood by identifying relationships between POCD and factors such as extended hospitalization, prolonged recovery of function, poor compliance with post-operative instruction and even an increased likelihood of re-admission [15,26,31].…”
Section: The Conceptualization Of Pocdmentioning
confidence: 99%